2021
DOI: 10.1007/s10143-020-01471-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management and outcome of adult patients with extracorporeal life support device–associated intracerebral hemorrhage—a neurocritical perspective and grading

Abstract: Intracerebral hemorrhage (ICH) is a devastating complication in patients treated with extracorporeal membrane oxygenation (ECMO) due to respiratory or cardiac issues. Neurosurgical evaluation and management of such cases has only insufficiently been studied. We conducted a retrospective, cohort study of adult patients treated with ECMO between January 2007 and January 2017 in a tertiary healthcare center. Demographics, clinical data, coagulation status, ICH characteristics, and treatment modalities were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The main findings of our study are as follows: (1) Over 10 years, we found ICRH in 21% of ARDS patients who had a brain CT scan during vv-ECMO support. (2) The majority of intracranial bleeding events were categorized as grade I/A in our study population [ 6 ]. (3) ICRH occurred in 35.4% of patients with and 16.7% of patients without COVID-19-associated ARDS during vv-ECMO support.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main findings of our study are as follows: (1) Over 10 years, we found ICRH in 21% of ARDS patients who had a brain CT scan during vv-ECMO support. (2) The majority of intracranial bleeding events were categorized as grade I/A in our study population [ 6 ]. (3) ICRH occurred in 35.4% of patients with and 16.7% of patients without COVID-19-associated ARDS during vv-ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO has evolved as a promising technique in the management of ARDS refractory to mechanical ventilation and adjunctive treatment [ 3 , 15 ]. Intracranial bleeding events are among the most feared ECMO-related complications and are associated with unacceptably high mortality [ 5 , 6 , 10 ]. The reasons for poor outcomes in patients with intracranial complications are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations